The greatest show on Earth : the evidence for evolution - Dawkins, Richard, 1941- (New York Times best sellers., 2009)
Sifting through rich layers of scientific evidence, Dawkins' "The Greatest Show on Earth" is a stunning counterattack on advocates of "Intelligent Design," explaining the evidence for evolution while exposing the absurdities of the creationist "argument."- Resumé vydavatel